Pembelajaran Menyimak Bahasa Arab dengan Memanfaatkan Teknologi Informasi dan Komunikasi - Prakasa, Fahreza (Indonesian Journal of Applied Linguistics Review, 2023)
Listening skills are an essential foundation for students in language learning, particularly in Arabic. These listening skills encompass the ability to comprehend spoken texts as a whole and the ability to focus on specific details, such as understanding information from speakers related to the details of what is conveyed, who is conveying it, when something happened, why something can occur, and how something can happen. Information and communication technology (ICT) is how technology is used to access, manage, and communicate information. This research employs qualitative descriptive methods with a literature review. Additionally, engaged observation has been conducted. In this era, the utilization of ICT is highly crucial, especially in the field of education. Many platforms can be used for online learning, such as zoom meetings, google meet, and learning management systems (LMS). In Arabic language listening instruction, the use of Information and Communication Technology (ICT) is highly effective. This is because students will experience the same level of comfort as they would when learning in a language lab or computer lab. This Arabic language listening instruction greatly aids students in enhancing one of the language skills they need to improve, which is listening skill.